2014
DOI: 10.1161/circulationaha.114.013603
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Thoracic Aortic Aneurysms and Dissection

Abstract: Editorial 2267I n this issue of Circulation, Sidloff and colleagues 1 have presented their findings that, among 18 World Health Organization member states over a period of 16 years (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), there has been a reduction in the age-standardized mortality from both thoracic aortic aneurysm and dissection. If one considers the United States, the United Kingdom, and Sweden, 3 countries that have published extensively on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
4
0
3
Order By: Relevance
“…It is clear that at least some of the impact on improving survival is related to these factors (18, 19). The overall operative mortality rate of 18.9% in this cohort, is consistent with the current literature (69, 1618, 2022). Mody et al demonstrated significant improvement in 30-day mortality for Medicare patients from 30.7% in 2000 to 21.4% in 2011, similar to an IRAD analysis where in-hospital mortality decreased from 25.0% in an era starting in 1996 to 18.4% currently (7, 8).…”
Section: Commentsupporting
confidence: 92%
See 1 more Smart Citation
“…It is clear that at least some of the impact on improving survival is related to these factors (18, 19). The overall operative mortality rate of 18.9% in this cohort, is consistent with the current literature (69, 1618, 2022). Mody et al demonstrated significant improvement in 30-day mortality for Medicare patients from 30.7% in 2000 to 21.4% in 2011, similar to an IRAD analysis where in-hospital mortality decreased from 25.0% in an era starting in 1996 to 18.4% currently (7, 8).…”
Section: Commentsupporting
confidence: 92%
“…The current literature is replete with contemporary outcomes from high volume hospitals or consortiums of aortic centers reporting improving outcomes with mortalities of 5–19% (35, 7, 9, 16, 17). These analyses suffer from the simple fact that their aortic teams, high volume aortic surgeons, and surgical and intensive care infrastructure may not be representative of the resources available to a majority of patients suffering TAAD.…”
Section: Commentmentioning
confidence: 99%
“…Type-B AD is usually managed medically with aggressive blood pressure control. Patients with AD tend to be 60 to 80-years-old-men [5][6][7][8][9][10]. In a review of 4428 patients from the International Registry of Acute Aortic Dissection (IRAD), 66% were men with mean age of 63-years [6].…”
Section: Case Discussionmentioning
confidence: 99%
“…Heilablóðfall greindist hjá tveimur sjúklingum (1,9%) en aðrir tveir sjúklingar létust innan 30 daga frá aðgerð (1,9% Tilviljanagreiningum hefur fjölgað á Vesturlöndum samhliða fjölgun myndrannsókna vegna óskyldra sjúkdóma í brjóstholi, til daemis við leit að aexlum í lungum eða við tölvusneiðmyndatöku á kransaeðum. 10 Ef rof eða flysjun (dissection) verður á gúlpnum er 30 daga dánarhlutfall allt að 25% hjá þeim sem ná lifandi í aðgerð, en rof er jafnframt langalvarlegasti fylgikvilli sjúkdómsins. 11,12 Því er reynt að gera skurðaðgerð á aeðargúlp áður en hann rofnar.…”
Section: Inngangurunclassified